Localized nitrogen supply facilitates rice yield and nitrogen use efficiency by enabling root-zone nitrogen distribution and root growth - Hu, Ren; Ding, Zijuan; Tian, Yingbing; Cao, Yuxian; Hou, Jun; Wang, Xuexia (Frontiers in Sustainable Food Systems, 2024)
Introduction Localized nitrogen (N) supply affects rice N uptake by influencing N release, and few studies have examined the effects of root zone N distribution and root growth on rice yield under localized N supply (LNS). Methods A two-year field experiment was conducted with six treatments: no N application, farmers’ fertilizer practice (FFP), and four LNS treatments, including two types of N fertilizer with urea (U) and controlled release urea (CRU) were mechanically side deep fertilized (SDF) or root zone fertilized (RZF) at 10 cm soil depth (US, UR, CRUS and CRUR treatments, respectively). Results Compared with FFP, the dry matter accumulation, N uptake, and yield of LNS increased by 27%, 21%, and 17%, respectively. For N fertilizer type, compared with U, the NH4+-N concentration, total root surface area, volume, average diameter, and root biomass of CRU were significantly increased by 50%, 43%, 53%, and 23%, respectively, which resulted in a significant increase in yield by 12%. Regarding the N application methods, the total surface area, volume, average diameter, and root biomass of SDF were significantly increased by 32%, 24%, 10%, and 25% compared with RZF, respectively. However, the NH4+-N under RZF was more stable and lasted longer, with a significant increase in NH4+-N concentration of 21% compared to the SDF. Moreover, CRUR increased yield, N agronomic use efficiency, and gross return by 3.15%, 5.62%, and 2.81%, respectively, compared to CRUS. Conclusion CRU should be selected as the recommended N fertilizer types, and the combination of CRU and RZF was the most effective choice for rice production.